Análise de conforto térmico em aeronaves: aspectos da radiação térmica no conforto térmico de uma aeronave - Liberatti, Maysa da Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The interest in the analysis of thermal comfort in aircrafts is growing more and more due to the special limitations of air conditioning systems and the thermal environment characteristics of an aircraft cabin. The main objective of this work is to calculate the Mean Radiant Temperature (tmr) in the heat exchange between the passenger and the cabin of an aircraft, using a model through a computational tool to facilitate the input data and calculations necessary to estimate the value of tmr. Firstly, a review will be presented with all the necessary concepts about heat exchange by radiation and thermal comfort. Studies will be presented in different way to obtain the mean radiant temperature at different points in the cabin. The work analyzes the heat exchange by radiation between the cabin and a passenger, which is sitting next to the cooler wall near the window. Through a model developed in a computational tool that allows through specific initial data, is going to be calculated the value of the tmr and the values of the Predicted Mean Vote (PMV) index and the predicted percentage dissatisfied (PPD) to estimate thermal comfort. Thus, data taken from tests and experiment performed on real commercial aircraft, aided in calculations performed through the model in order to make the results obtained as close as possible to the real values. Finally, a comparison was made between the values obtained in the studies in which this work was based on and the values found through the applied methodology. Therefore, making possible to understanding the importance of the use of measuring instruments and the less simplification possible in the calculation, for a greater accuracy of the value of mean radiant temperature, and the impact on the index of thermal comfort

A atenção sobre a análise do conforto térmico em aeronaves cresce cada vez mais devido a limitações especiais dos sistemas de climatização e das características do ambiente térmico de uma cabine de aeronave. O objetivo principal deste trabalho visa calcular a temperatura média radiante (tmr) na troca de calor que ocorre entre o passageiro e a cabine de uma aeronave, utilizando um modelo através de uma ferramenta computacional para facilitar os dados de entrada e os cálculos necessários para se estimar o valor da tmr. Primeiramente, será apresentado uma revisão com todos os conceitos necessários sobre trocas de calor por radiação e conforto térmico. Serão apresentados estudos realizados de diferentes maneiras para se obter a temperatura média radiante em diferentes pontos da cabine. O trabalho analisa as trocas de calor por radiação de um passageiro com a cabine, que esteja sentado ao lado da parede mais fria próxima a janela, através de um modelo desenvolvido em uma ferramenta computacional que permite através de dados específicos iniciais, calcular o valor da tmr e os valores dos índices, voto médio estimado (PMV) e porcentagem de pessoas insatisfeitas (PPD) para estimar o conforto térmico. Dessa forma, dados retirados de ensaios e testes realizados em aeronaves comerciais reais, auxiliaram nos cálculos realizados através do modelo com a finalidade de tornar os resultados obtidos os mais próximos possíveis dos valores reais. Por fim, foi realizada uma comparação entre os valores obtidos nos estudos em que este trabalho se baseou, e os valores encontrados através da metodologia aplicada, tornando possível o entendimento da importância da utilização de instrumentos de medição e da menor simplificação possível nos cálculos, para uma maior precisão do valor da temperatura média radiante e do seu impacto nos índices de conforto térmico
Aircraft thermal comfort analysis: aspects of thermal radiation on the thermal comfort of an aircraft
Keywords: Conforto termico; Calor - Transmissão; Ar condicionado; Aeronáutica comercial; Heat Transmission